2020
DOI: 10.1016/j.yebeh.2019.106717
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experience of wearing multimodal sensor devices intended to detect epileptic seizures: A qualitative analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 19 publications
(32 reference statements)
3
49
1
Order By: Relevance
“…A further advantage of our method is that it operates remotely, without sensors attached to the individual. A survey on first‐hand experiences of people with epilepsy using wearable devices during a clinical stay indicated that most participants found the devices convenient 19 . The presence of wires, bulky size, discomfort, and need for support did, however, moderate experience.…”
Section: Discussionmentioning
confidence: 99%
“…A further advantage of our method is that it operates remotely, without sensors attached to the individual. A survey on first‐hand experiences of people with epilepsy using wearable devices during a clinical stay indicated that most participants found the devices convenient 19 . The presence of wires, bulky size, discomfort, and need for support did, however, moderate experience.…”
Section: Discussionmentioning
confidence: 99%
“…3,30,31 However, a lot of attention should be given to device design in order to address the requirements and preferences of PWE and caregivers, since these factors influence acceptance and long-term engagement, which is essential to allow novel technologies to successfully meet the needs of PWE. Multiple factors have been explored in studies investigating user preferences 3,24,25,[27][28][29][30][31][32][33][34] and, to a lesser extent, direct experiences with digital tools 32,34 ; these are summarized below. Unobtrusiveness is also a desired feature, so that the detection device does not call unwanted attention to the user.…”
Section: Caregivers Want From Seizure-detection Devices?mentioning
confidence: 99%
“…24 Wires, stickers, patches, bulky or cumbersome shapes, as well as the presence of flashing lights lead to unwanted visibility. 32 Discreet, inconspicuous devices that can be worn and covered with clothes are largely favored. 30 However, in the context of exclusively night-time or home use, appearance and visibility are less important and sensors under the mattress and more unconventional designs may be considered acceptable.…”
Section: Caregivers Want From Seizure-detection Devices?mentioning
confidence: 99%
See 2 more Smart Citations